Práticas educativas em diabetes na Estratégia Saúde da Família (ESF) do município de Manaus/AM - Gomes, Eliana Marques [UNIFESP] (2013)
The education in health consists in one of the main elements of the promotion in health, being essential the interdisciplinary work of the health team. The educational practices in diabetes are a tool that must concentrate itself in innovative actions, with the intention of formation of the critical conscience about the health and not only in changes or repasses of information, that contributes just a little to the improvement of the quality of life of the population. This research had as general objective: to verify the educational practices in diabetes developed in the Strategy “Health of the Family-(SHF)” in the city of Manaus in the west district are based on the principles of promotion of health, and specific objectives: to verify how the educational practices in diabetes happen; to verify how educational actions in diabetes are developed and planned; to identify which the contents and types of strategies used in those educational practices; to discover the easiness and difficulties of accomplishment of the educational practices. It is a study of descriptive-exploratory character in the qualitative and quantitative approaches. The subjects were 34 nurses of the Units of Health of the Strategy “Health of the Family”, of the west zone. For collecting data we opted for interviews with semi-structured questionnaire technique. The analysis allowed us to select four thematic focuses and 16 subthemes: The educational practice in the unit of health (planning of the activities, the professional involvement, the professional training, the scenery of the activities, the approached theme; accomplished activities); Strategies and educational resources (the importance of the teaching strategy), didactic resources; The nurse's glance to the objectives of the educational practice (knowledge of the disease, prevention of the complications, changes of habits, self-care, patient and professional team, life quality); easiness and difficulties in educational practice. The results allowed us to identify predominant aspects in the educational practices in health developed in Brazil, a strong tendency of practices still traditional, and predominant of healing characteristics, preventive and more welfare assistance than promotional. Educational practices were also observed developed with methodologies and no innovative didactic resources. In face of those results found, reflections are necessary on the knowledge systematized in the educational practices in diabetes. Practices that include the diabetic person in the social process, reflexive and committed with their knowledge about the disease, and so, contribute in the process of social change and quality of those people's life.